Celastrol Dilates and Counteracts Ethanol-Induced Constriction of Cerebral Arteries - North, Kelsey (J Pharmacol Exp Ther, 2020)
The increasing recognition of the role played by cerebral artery dysfunction in brain disorders has fueled the search for new cerebrovascular dilators. Celastrol, a natural triterpene undergoing clinical trials for treating obesity, exerts neuroprotection, which was linked to its antioxidant/anti-inflammatory activities. We previously showed that celastrol fit pharmacophore criteria for activating calcium- and voltage-gated potassium channels of large conductance (BK channels) made of subunits cloned from cerebrovascular smooth muscle (SM). These recombinant BK channels expressed in a heterologous system were activated by celastrol. Activation of native SM BK channels is well known to evoke cerebral artery dilation. Current data demonstrate that celastrol (1–100 µM) dilates de-endothelialized, ex vivo pressurized middle cerebral arteries (MCAs) from rats, with EC(50) = 45 µM and maximal effective concentration (E(max))= 100 µM and with MCA diameter reaching a 10% increase over vehicle-containing, time-matched values (P < 0.05). A similar vasodilatory efficacy is achieved when celastrol is probed on MCA segments with intact endothelium. Selective BK blocking with 1 μM paxilline blunts celastrol vasodilation. Similar blunting is achieved with 0.8 mM 4-aminopirydine, which blocks voltage-gated K(+) channels other than BK. Using an in vivo rat cranial window, we further demonstrate that intracarotid injections of 45 μM celastrol into pial arteries branching from MCA mimics celastrol ex vivo action. MCA constriction by ethanol concentrations reached in blood during moderate-heavy alcohol drinking (50 mM), which involves SM BK inhibition, is both prevented and reverted by celastrol. We conclude that celastrol could be an effective cerebrovascular dilator and antagonist of alcohol-induced cerebrovascular constriction, with its efficacy being uncompromised by conditions that disrupt endothelial and/or BK function. SIGNIFICANCE STATEMENT: Our study demonstrates for the first time that celastrol significantly dilates rat cerebral arteries both ex vivo and in vivo and both prevents and reverses ethanol-induced cerebral artery constriction. Celastrol actions are endothelium-independent but mediated through voltage-gated (K(V)) and calcium- and voltage-gated potassium channel of large conductance (BK) K(+) channels. This makes celastrol an appealing new agent to evoke cerebrovascular dilation under conditions in which endothelial and/or BK channel function are impaired.